Observation on the clinical effectiveness of intermuscular suture combined with fullthickness advancement flap in the treatment of suprasphincteric anal fistula: a series of 33 cases - Yang Xiaoyuan; Chen Wenping; Lin Wanlin; Ma Qiaoling; Zhang Lei; Zhu Jiandong; Zhao Shen; Yang Limin; Ma Zhiteng; Huang Shaoling; Yuan Yuewen (结直肠肛门外科)
[Objectives] To investigate the clinical effectiveness of intermuscular suture combined with full-thickness advancement flap in the treatment of suprasphincteric anal fistula. [Methods] A retrospective analysis was conducted on the clinical data of 33 patients with suprasphincteric anal fistula who underwent intermuscular suture combined with fullthickness advancement flap in our department from September 2020 to June 2023. The treatment outcomes (cure or treatment failure), disease-related information, anal function, and patient’s satisfaction with surgical treatment were recorded. [Results] All 33 patients successfully completed the surgery. Postoperative follow-up ranged from 90 to 1, 095 days, with a median follow-up time of 210 (90, 840) days. A total of 29 patients achieved cure, while 4 patients had treatment failure. There were no significant differences in the history of abscess/anal fistula surgery, the presence of horseshoe anal fistula, the presence of fistula branches, or the presence of abscess between the cured patients and those with treatment failure (P>0.05). The median preoperative Wexner incontinence score was 0 (0, 2) for all 33 patients, which was significantly different from the corresponding score of 0 (0, 4) at 3 months postoperatively (P<0.05). At the 3-month postoperative follow-up, 31 patients expressed satisfaction with the surgical outcome, while 2 patients expressed dissatisfaction. [Conclusion] The short-term clinical effectiveness of intermuscular suture combined with fullthickness advancement flap in the treatment of suprasphincteric anal fistula is good.